2012
DOI: 10.4028/www.scientific.net/amr.524-527.1136
|View full text |Cite
|
Sign up to set email alerts
|

The Extraction of Potassium from Feldspar by Molten Salt Leaching Method with Composite Additives

Abstract: Effects of ratios of feldspar to CaCl2 to NaCl, roasting temperature ,roasting time and particle size on the melting-out rate of potassium from feldspar was studied by roasting. Results showed that the highest melting-out rate of potassium reached at 95.35% under the ratio of 1.8:1.1:0.6 of feldspar to CaCl2 to NaCl, particle size 220mesh, roasting temperature 800°C, roasting time 1h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Figure 6 shows the results of the dissolution experiments in which the sample was roasted at temperatures of 650, 750, 850, and 950 • C and for 30, 60, 120, and 180 minutes. Researchers who conducted similar potassium extraction studies stated that the highest recoveries were obtained at 800 • C [5,6] and 900 • C [4,7,8,10,11,13]. Yuan et al [9] observed a decrease in the potassium yields at elevated temperatures, similar to the findings of this study.…”
Section: Effect Of Roasting Temperature and Durationsupporting
confidence: 85%
See 1 more Smart Citation
“…Figure 6 shows the results of the dissolution experiments in which the sample was roasted at temperatures of 650, 750, 850, and 950 • C and for 30, 60, 120, and 180 minutes. Researchers who conducted similar potassium extraction studies stated that the highest recoveries were obtained at 800 • C [5,6] and 900 • C [4,7,8,10,11,13]. Yuan et al [9] observed a decrease in the potassium yields at elevated temperatures, similar to the findings of this study.…”
Section: Effect Of Roasting Temperature and Durationsupporting
confidence: 85%
“…Nayak et al reported that 65% of the potassium could be dissolved from 13% K 2 O bearing rock with roasting at 850-900 • C together with MgSO 4 +CaCO 3 at a ratio of 1:0.7:3 to feldspar, with the feldspar having a grain size under 63 microns [4]. Zhang et al [5] claimed that when feldspar:CaCl 2 :NaCl roasted together at a ratio of 1.8:1.1:0.6 at 800 • C for 1 hour, the potassium extraction reached 95.5%, starting from 14.81% K 2 O bearing feldspar with a grain size under 70 microns. Xie et al [6] stated that 84.7% potassium recovery was obtained from 9.3% K 2 O bearing feldspar, minus 45 microns feldspar ore with CaCl 2 , by roasting at 800 • C for 1 hour.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal treatment whereby high-temperature molten salt is used as a fluxing agent for extraction of potassium from K-bearing ores was found to be the most effective method due to its large potential for the rapid release and high recovery of potassium from the silicate structure. ,,, However, thermal treatment is an energy-intensive process compared with other methods in part because of the high-temperature calcination and also because of the latent heat required to convert a solid salt to a liquid phase. Decomposition of K-bearing ores with various salts has been experimentally investigated by various research groups in Brazil, ,, India, ,, and China. ,− A number of potential reagent candidates have been identified to solubilize K-bearing ores through roasting. The detailed results for optimum conditions at which the highest potassium recovery was achieved are presented in Table .…”
Section: Introductionmentioning
confidence: 99%
“…The potassium present in orthoclase and microcline phases of FS reacts with the calcium chloride to produce potassium chloride as it has the minimum standard free energy change for the formation as compared to other metal chlorides . Molten salt additives are considered as a better fluxing agent for the materials comprising silicate ores . The probable reaction during roasting of feldspar with calcium chloride is as follows …”
Section: Resultsmentioning
confidence: 99%
“…25 Molten salt additives are considered as a better fluxing agent for the materials comprising silicate ores. 26 The probable reaction during roasting of feldspar with calcium chloride is as follows…”
Section: Particle Size Effect On Extractionmentioning
confidence: 99%